2019
DOI: 10.1073/pnas.1816056116
|View full text |Cite
|
Sign up to set email alerts
|

Placental mitochondria adapt developmentally and in response to hypoxia to support fetal growth

Abstract: Mitochondria respond to a range of stimuli and function in energy production and redox homeostasis. However, little is known about the developmental and environmental control of mitochondria in the placenta, an organ vital for fetal growth and pregnancy maintenance in eutherian mammals. Using respirometry and molecular analyses, the present study examined mitochondrial function in the distinct transport and endocrine zones of the mouse placenta during normal pregnancy and maternal inhalation hypoxia. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 46 publications
4
75
1
Order By: Relevance
“…While further studies are needed to firmly establish a link between changes in bioenergetics in the male placenta and disturbances in fetal metabolic status, the co-occurrence of these phenomena suggest that they are related. Importantly, placental mitochondria are structurally and functionally diverse within the organ's regions and these mitochondrial subpopulations may also respond differently depending on gestational age [ 20 , 63 ]. Additional work is needed to elucidate how sex and specific placental cell populations interact to support fetal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While further studies are needed to firmly establish a link between changes in bioenergetics in the male placenta and disturbances in fetal metabolic status, the co-occurrence of these phenomena suggest that they are related. Importantly, placental mitochondria are structurally and functionally diverse within the organ's regions and these mitochondrial subpopulations may also respond differently depending on gestational age [ 20 , 63 ]. Additional work is needed to elucidate how sex and specific placental cell populations interact to support fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Placental mitochondrial dysfunction has also been theorized to mediate sexually dimorphic fetal programming due to the mitochondria's importance in resource availability, oxidative stress, and steroidogenesis, as well as their relative abundance in the placenta [ 20 , 21 ]. Numerous studies have reported relationships between pregnancy complications and altered respiratory chain complex activity [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are also important to trophoblast function, with alterations in trophoblast mitochondrial function evident in conditions associated with offspring obesity, including preeclampsia and gestation diabetes [91,92]. The decrease in trophoblast mitochondrial respiration in gestational diabetes seems mediated by an increase in ceramide [92], with ceramide also shown to increase mitochondrial fusion and mitophagy in preeclampsia trophoblasts [93].…”
Section: Melatonin and Mitochondriamentioning
confidence: 99%
“…In contrast, preeclampsia may be associated with an increase in trophoblast mitochondrial respiration, although with a decrease in respiratory reserve capacity [94]. Preclinical studies indicate that there may differential effects on mitochondrial function in different placental regions [91]. As well as immune cells, trophoblast mitochondrial function regulation by local and circadian melatonin are clearly relevant to placental changes that increase offspring obesity risk.…”
Section: Melatonin and Mitochondriamentioning
confidence: 99%
“…The adverse intrauterine environment caused by maternal malnutrition and placental hypoxia has been regarded as the main cause. 3,4 Growth restriction in fetuses causes lower birth weight and increased risk for the development of severe disorders later in life, such as mental illness, 5,6 obesity, cardiovascular, and renal disease. 7,8 According to previous studies on the Dutch Hunger Winter, early gestational exposure to the Dutch Hunger Winter of 1944-1945 was associated with an increased risk of schizophrenia in offspring, and the risk of schizophrenia was twice as high as that of the control group.…”
Section: Introductionmentioning
confidence: 99%